COMPARATIVE ANALYSIS OF CORROSION RESISTANCE OF GALVANNEALED STEEL IN WET-DRY CYCLE AND FULL IMMERSION CONDITIONS IN SOLUTIONS CONTAINING CHLORIDE AND SULPHATE IONS - Fikri Fauzan Hasrul, Muhammad
Galvannealed steel is widely used for car body materials. Galvannealed steel is made by coating the steel using zinc and then annealed. One problem with galvannealed steel is that it can be corroded, mainly due to the presence of chloride and sulfate ions. In coastal areas, the environment have significant humidity changes that cause thin electrolyte layers on the surface galvannealed steel to change over time. Therefore it is necessary to test the galvannealed steel on the environment of chloride and sulfate solutions with a variety of full immersion and wet-dry cycle immersion treatments. Tests were carried in NaCl solution, Na2SO4 and a mixture of both. Immersion was carried out for 7 days with 12 hours wet time and 12 hours dry time for wet-dry cycle variations. Weight loss calculation was carried out to determine the corrosion rate. In addition, electrochemical cyclic polarization and electrochemical impedance specroscopy tests were also carried out using potentiostat. Characterization was performed by scanning electron microscope and x-ray diffraction. XRD analysis shows that intermetallic phase Fe13Zn126 was formed and Zn5Cl2(OH)6.H2O was formed after 7 days immersion in chloride solution. From the results of the immersion test, the rate of corrosion of steel in a solution of chloride, sulfate and mixture were 1,156; 1,701; and 0,844 mm/year repectively for full immersion. Whereas for wet-dry cycle are 1,682; 2,825; and 1,195 mm/year respectively. From tafel extrapolation, the corrosion rate at full immersion in the chloride, sulfate, and mixture solution were 0.034; 0.044; and 0.020 mm/year. Whereas in the wet-dry cycle the corrosion rate is 0.112; 0,111; and 0.093 mm/year. Corrosion rate obtained at the wet-dry cycle is faster than full immersion. This is due to the degradation of passive layers and uneven deposition of salt in dry conditions. From the cyclic polarization curve, the pit formation after 7 days immersion was seen both full immersion and wet-dry cycle. The highest corrosion rate was occurred in chloride solution in wet-dry cycle immersion. The appropriate circuit model for full immersion is (Rs (CPEox (Rox (CPEdl / Rct) which shows the formation of a passive zinc oxide layer. Whereas in the wet-dry cycle variation in chloride and sulfate solutions, the appropriate circuit model is (Rs (CPEpor) (CPEox (Rox (CPEdl / Rct) which shows the formation of zinc oxide that is not protective so that the steel begins to corrode.